Case report: Diabetic muscle infarction with diabetic ketoacidosis: A rare complication of diabetes - Tang, Jun; Sun, Li; Huang, Qi; Wu, Yu-Wen; Li, Xin; Deng, Hao-Hua; Sun, Jia-Zhong; Dai, Zhe; Xu, Yan-Cheng (Frontiers in Endocrinology, 2023)
Background Diabetic muscle infarction (DMI), which is also referred to as diabetic myonecrosis, is a rare and long-term complication of poorly controlled diabetes mellitus, while we found that acute diabetes decompensation, such as diabetic ketoacidosis (DKA), could also stimulate the occurrence and development of DMI. Case presentation A 23-year-old woman with type 1 diabetes presented with a 10-day history of nausea, vomiting, pain, and swelling of her left leg. Her urine ketone test was positive. The 3-beta-hydroxybutyrate and leukocyte counts and creatine kinase levels were elevated. Magnetic resonance imaging of the left thigh revealed extensive deep tissue oedema and an increase in the T2 signal in the involved muscles. Once the diagnosis of DMI was made, she was managed with rest, celecoxib, clopidogrel and aggressive insulin therapy. Three months after treatment, the patient reported complete resolution of symptoms. Conclusion DMI is a rare DM complication with a high recurrence rate, commonly presenting with chronic complications, while our case report shows that acute diabetes decompensation, such as DKA, can stimulate the occurrence and development of DMI. Timely diagnosis and appropriate treatment could shorten the recovery time.